X.DÁWLETNAZAROV POEZIYASÍNDA OMONIM, SINONIM HÁM ANTONIMLERDIŃ STILLIK QOLLANÍLÍWÍ - Allanazarov, Esbergen Esbosınovish; Esbergenova, Bağdagul Perdebaevna (SCIENCE and SOCIETY, 2026)
In the article, one of the linguistic unic of our language is devoted to the event of the use of omonims, sinonims end antonims unic in the artistic language. In the works of X.Dawletnazarov, some details are given concerning the peculiarities of the meaning of the word in use.